Screening of Antitubercular Compound Library Identifies Inhibitors of Mur Enzymes in Mycobacterium tuberculosis. (January 2020) - Eniyan, Kandasamy; Rani, Jyoti; Ramachandran, Srinivasan; Bhat, Rahul; Khan, Inshad Ali; Bajpai, Urmi
The rapid rise in the emergence of multidrug-resistant (MDR) and extensively drug-resistant (XDR) strains of Mycobacterium tuberculosis (Mtb) mandates the discovery of novel tuberculosis (TB) drugs. Mur enzymes, which are identified as essential proteins in Mtb and catalyze the cytoplasmic steps in the peptidoglycan biosynthetic pathway, are considered potential drug targets. However, none of the clinical drugs have yet been developed against these enzymes. Hence, the aim of this study was to identify novel inhibitors of Mur enzymes in Mycobacterium tuberculosis . We screened an antitubercular compound library of 684 compounds, using MurB and MurE enzymes of the Mtb Mur pathway as drug targets. For experimental validation, the top hits obtained on in silico screening were screened in vitro, using Mtb Mur enzyme-specific assays. In all, seven compounds were found to show greater than 50% inhibition, with the highest inhibition observed at 77%, and the IC50 for these compounds was found to be in the range of 28–50 μM. Compound 5175112 showed the lowest IC50 (28.69 ± 1.17 μM), and on the basis of (1) the binding affinity, (2) the stability of interaction noted on molecular dynamics simulation, and (3) an in vitro assay, MurE appeared to be its target enzyme. We believe that the overall strategy followed in this study and the results obtained are a good starting point for developing Mur enzyme-specific Mtb inhibitors.